2020
DOI: 10.1155/2020/8812443
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection of Ascorbic Acid, Dopamine, and Uric Acid Using a Novel Electrochemical Sensor Based on Palladium Nanoparticles/Reduced Graphene Oxide Nanocomposite

Abstract: A fresh strategy based on two-step electrochemical reduction for the fabrication of palladium nanoparticles/reduced oxide nanocomposite-modified glass carbon electrode (PdNPs/rGO/GCE) was established in this study. Field emission scanning electron microscopy (FESEM) images showed that spherical PdNPs were evenly distributed on the surface of rGO-modified electrode (rGO/GCE), and the introduction of PdNPs has no effect on the morphology of rGO. Electrochemical impedance spectroscopy (EIS) studies revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 50 publications
(30 reference statements)
1
14
0
Order By: Relevance
“…1. Our DFT calculation using the GGA-PBE functional with vdW-DF2 correction found that the stability of GO5-zigzag-B > GO5-para > GO5-zigzag-A > GO5-armchair was with a similar trend to the previous DFT study [20]. The most stable epoxy-functionalized GO, GO5-zigzag-B, was with an epoxy group at the opposite side of the graphene plane from the other four epoxy groups.…”
Section: Graphene Oxide Configurationsupporting
confidence: 77%
See 1 more Smart Citation
“…1. Our DFT calculation using the GGA-PBE functional with vdW-DF2 correction found that the stability of GO5-zigzag-B > GO5-para > GO5-zigzag-A > GO5-armchair was with a similar trend to the previous DFT study [20]. The most stable epoxy-functionalized GO, GO5-zigzag-B, was with an epoxy group at the opposite side of the graphene plane from the other four epoxy groups.…”
Section: Graphene Oxide Configurationsupporting
confidence: 77%
“…These made graphene an ideal material for developing biosensors. A number of studies have reported the electrode modification to improve the simultaneous determination of AA, DA, and UA in the CV and differential pulse voltammetry (DPV) experiments [9][10][11][12][13][14][15][16][17][18][19][20][21], e.g., the use of multilayer graphene nanoflake films (MGNFs) [9], graphitic sheets or multi-walled carbon nanotube/metal composites [10,12,13,[16][17][18][19][20], and conducting polymers [11,14,15,21]. Moreover, electrical [22] and chemical [23] reduced graphene oxide (rGO) were also employed for AA/DA/UA detections due to the better conductivity than GO and their cost effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…These made graphene an ideal material for developing biosensors. Many studies have reported electrode modification to improve the simultaneous determination of AA, DA, and UA in the CV and differential pulse voltammetry (DPV) experiments [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], e.g., the use of multilayer graphene nanoflake films (MGNFs) [ 10 ], graphitic sheets or multi-walled carbon nanotube/metal composites [ 11 , 13 , 14 , 17 , 18 , 19 , 20 , 21 ], and conducting polymers [ 12 , 15 , 16 , 22 ]. Moreover, electrical [ 23 ] and chemical [ 24 ] reduced graphene oxides (rGO) were also employed for AA/DA/UA detections due to the better conductivity than GO and their cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively low costs and simple measurement procedures, requiring a three-electrode system and a potentiostat to scan for the redox potentials that return the signal of molecules, led to the possibility of developing the portable sensing platforms [17][18][19]. Many studies showed that using a cyclic voltammetry (CV) or differential pulse voltammetry (DPV) with glassy carbon electrodes (GCE) can detect AA, DA, and UA up to the micromolar limit of detection [20][21][22]. However, these electrochemical techniques failed to simultaneously detect AA, DA, and UA due to overlapping oxidation peaks, which might cause false-positive detection cases in clinical uses [23][24][25].…”
Section: Introductionmentioning
confidence: 99%